Peran Pemerintah dalam Pemberdayaan Lanjut Usia di Kabupaten Sidoarjo - Ramadhani Bondan Puspitasari; Arsiyah Arsiyah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
This study aimed to describe the role of government in empowering the elderly in Sidoarjo and its supporting and inhibiting factors. This research is used by qualitative description. This study concluded that the government’s Sidoarjo Regency in implementing empowerment elderly quite good. It is supported by mental spiritual and religious guidance, health aspects like clinic and gymnastics, skills training such as crafts from recycled materials, ease in using facilities, public facilities and infrastucture, as well as social assistance in the form of cash RP.300.000 for poor elderly and unhealthy elderlys. Meanwhile, inhibiting factors first, coordination between three local work unit namely Social Department and Labor; Public Health Service; and Community Empowerment, Women and Family Planning Department. Second, data wasn’t valid related with neglected elderly in the villages. Third, elderly still had low awareness about importance of empowerment for their lives.